Anatomy of the sacroiliac joint with relation to the lumbosacral trunk: Is there sufficient space for a two-hole plate? - Michał Kułakowski; Karol Elster; Paweł Reichert; Aleksandra Królikowska; Joanna Jerominko; Paweł Ślęczka; Magdalena Grzonkowska; Michał Szpinda; Mariusz Baumgart (PLoS ONE)
Dislocations of the sacroiliac joint (SIJ) are treated with iliosacral screws or anterior plating. The study aimed to investigate the course of the lumbosacral trunk with reference to SIJ and determine whether is there sufficient space for two screws through the sacrum while performing anterior plating. Sixty patients, who underwent an MRI of the lumbar spine were included in our study. The three transverse LT-SIJ distances were measured at the three points (A, B, and C). We also analyzed 60 CT pelvic scans at points A, B, and C in order to measure: the vertebral canal-to-SIJ distance, the sacrum's pelvic-to-dorsal surface sagittal distance, and the median plane-to-SIJ angle. The mean transverse LT-SIJ distances at points A, B, and C were 20.0 ± 3.05 mm, 17.9 ± 3.20 mm, and 12.3 ± 2.49 mm, respectively. Based on CT analyses, the vertebral canal-to-SIJ distances were 30.5 ± 7.65 mm at point A, 21.4 ± 5.05 mm at point B and 15.7 ± 6.05 mm at point C. The sacrum's pelvic-to-dorsal surface sagittal distances reached values: 35.1 ± 11.62 mm at point A, 52.5 ± 10.58 mm at point B, and 57.5 ± 7.79 mm at point C. The median plane-to-SIJ angles measured 31.4 ± 4.82 degrees at point A, 26.6 ± 3.77 degrees at point B and 21.3 ± 3.25 mm at point C. Proximally, the safe zone for applying an anterior plate of SIJ is 20.0 mm. Since both the safe zone and safe corridor taper distally, surgeons may securely use one screw of gradually increased length towards the distal direction of SIJ, with inclination of 30 degrees in relation to the median plane of the lesser pelvis.